Impact of corporate governance on intellectual capital efficiency and financial performance - Muhammad Abdul Majid Makki; Suleman Aziz Lodhi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
This study develops a structural model linking corporate governance, intellectual capital efficiency and financial performance then verifies it through structural equation modeling based on partial least square. Corporate governance has been conceptualized and measured through chief executive officer's duality, ratio of non executive directors, directors' ownership, executives' remuneration and number of shareholders. Intellectual capital efficiency is computed through Value Added Intellectual Coefficient (VAICTM), and financial performance is represented through return on investment, return on equity and net profit after tax. The study reveals and determines the existence of critical structural relationship among corporate governance, intellectual capital efficiency and financial performance. The study concludes that corporate governance does not improve financial performance directly; rather corporate governors can enhance it significantly through exploiting intellectual capital resources. The study provides empirical evidence that a firm with good corporate governance measures enhances IC efficiency that ultimately generates more return on investment, return on equity and net profit.
Keywords: 330; Value Added Intellectual Coefficient (VAIC); partial least square; frequency of board meetings; Pakistan